An Traffic Control Method Based on the Real-Time Detector Delay - Liu, Bohang; Zhang, Tong; Li, Qingbing; Wang, Lijuan (Communications - Scientific Letters of the University of Zilina, 2010)
This paper puts forward a new single intersection control optimization method based on real-time delays by using the new technology of traffic detection. With this method the delay data (including parking delay, acceleration and deceleration delays) of vehicles and speed of the vehicles at the stop bar in every cycle can be detected real-timely. Thus, we can change the cycle length, total split, yellow time and all red time according to the analysis of the reasons of delay changes so as to optimize the traffic signal timing. Compared with traditional methods, this method can effectively deal with the situation that the traffic control scheme does not conform to the actual situation, resulting from the change of the road capacity under the conditions of rain, snow or fog, etc. The good effect can be seen in the example of this research as it effectively reduced delay by 19 % on average.
Keywords: real-time detector delay; traffic control; traffic control results